2018
DOI: 10.1111/iep.12301
|View full text |Cite
|
Sign up to set email alerts
|

Non‐alcoholic steatohepatitis aggravates nitric oxide synthase inhibition‐induced arteriosclerosis in SHRSP5/Dmcr rat model

Abstract: Summary Non‐alcoholic steatohepatitis (NASH) is linked to increased cardiovascular risk, independent of the broad spectrum of metabolic syndrome risk factors. Stroke‐prone (SP) spontaneously hypertensive rats (SHRSP5/Dmcr) fed a high‐fat and high‐cholesterol (HFC) diet developed hepatic lesions similar to those in human NASH pathology. These rats simultaneously developed lipid deposits in the mesenteric arteries, cardiac fibrosis, endothelial dysfunction and left ventricle (LV) diastolic dysfunction. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…According to this case, it was suggested that intractable coronary artery disease observed in diabetic patients might be due to triglyceride accumulation centered on the media region of the coronary wall, unlike conventional atherosclerosis characterized by cholesterol accumulation [ 46 , 47 ]. As another form of ectopic fat deposition, nonalcoholic steatohepatitis (NASH) aggravates nitric oxide synthase (NOS) inhibition-induced arteriosclerosis in NASH model rats [ 48 ]. It is possible that ectopic fat accumulation in coronary arteries might also cause the dysregulation of NOS, which is inhibited by asymmetric dimethylarginine [ 49 ], resulting in coronary artery disease.…”
Section: Ectopic Fat In Heartmentioning
confidence: 99%
“…According to this case, it was suggested that intractable coronary artery disease observed in diabetic patients might be due to triglyceride accumulation centered on the media region of the coronary wall, unlike conventional atherosclerosis characterized by cholesterol accumulation [ 46 , 47 ]. As another form of ectopic fat deposition, nonalcoholic steatohepatitis (NASH) aggravates nitric oxide synthase (NOS) inhibition-induced arteriosclerosis in NASH model rats [ 48 ]. It is possible that ectopic fat accumulation in coronary arteries might also cause the dysregulation of NOS, which is inhibited by asymmetric dimethylarginine [ 49 ], resulting in coronary artery disease.…”
Section: Ectopic Fat In Heartmentioning
confidence: 99%
“…Furthermore, the SHRSP5/Dmcr rats fed an HFC diet and administrated nitric oxide (NO) synthesis inhibitor Nω-Nitro-L-arginine methyl ester hydrochloride (L-NAME) induced coronary smooth muscle cell (SMC) hypertrophy or arterial lipid deposition, and developed LV systolic dysfunction, asynergy, and replacement fibrosis. On the other hand, the SHRSP5/Dmcr rats fed an SP diet and administered L-NAME, did not present NASH pathology, or any cardiac or vascular damage [6]. These findings demonstrate that NASH aggravates the cardiovascular risk in SHRSP5/Dmcr rats.…”
Section: Introductionmentioning
confidence: 59%
“…The SHRSP5/Dmcr rat model, which has congenital hypertension, induces NASH, lipid deposition at the mesenterial artery, and hyperlipidemia due to HFC diet [15,16]. In addition, we previously reported that the SHRSP5/Dmcr rat model fed an HFC diet and administered L-NAME, demonstrated characteristics similar of those of the ischemic heart disease; (1) LV systolic dysfunction associated with asynergy, (2) replacement fibrosis caused by shedding of cardiomyocytes, and (3) coronary SMCs hypertrophy and arterial lipid deposition caused by endothelial dysfunction [6]. However, the intermediary factors between NASH and ischemic heart disease were not identified.…”
Section: Discussionmentioning
confidence: 90%
“…NAFLD can be categorized as simple liver steatosis (nonalcoholic fatty liver: NAFL) or nonalcoholic steatohepatitis (NASH) with intralobular inflammation, ballooning degeneration of hepatocytes, and fibrosis [ 1 ]. Excess hepatic fat deposition in patients with NAFLD is associated with an increased risk of diabetes, hypertension, and cardiovascular events, which are caused by lipotoxic inflammatory mediators targeting the vascular endothelium of the liver and cardiovascular system [ 2 ]. Apart from lifestyle modifications through diet and exercise, currently, no specific treatments for NAFLD are known.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports from Zhang et al [ 9 ] and Toblli et al [ 10 ] show that angiotensin-converting enzyme (ACE) inhibitors prevent not only liver-related events in NAFLD in humans but also fatty liver and fibrosis in an obese zucker NASH rat model. These results may indicate that hepatic and cardiovascular endothelial dysfunction potentially represents at least one of the common underlying etiologies of NASH pathology [ 2 , 8 ]. NO-mediated signaling, including that induced through dietary and pharmacological means, could possibly provide preventive and therapeutic options for this disease.…”
Section: Introductionmentioning
confidence: 99%